Efficacy of iguratimod in the treatment of patients with palindromic rheumatism ineffective to methotrexate or hydroxychloroquine - Chen, Mengjie; Cheng, Yongjun; Jin, Guiyao; Tu, Yuren; Zhang, Qi; Zhang, Chuanfu; Wang, Wenlong (Frontiers in Immunology, 2025)
IntroductionPalindromic Rheumatism (PR) is a rare form of arthritis characterized by recurrent episodes of joint and periarticular inflammation. Given the paucity of established treatment guidelines due to its rarity and complex pathogenesis, we aimed to analyze the efficacy and safety of iguratimod (IGU) in the treatment of refractory PR.MethodsThis retrospective study included patients with PR who attended the First People’s Hospital of Wenling between January 2019 and September 2023. 32 patients with poor response to methotrexate (MTX) and hydroxychloroquine (HCQ) were enrolled and were switched to IGU 25 mg twice daily alone or in combination with MTX 10 mg weekly. The primary outcomes measured included the frequency and duration of disease attacks over a three-month period. Complete remission was defined as no attacks within three months, partial remission as a reduction of at least 50% in attack frequency, and no remission as less than a 50% reduction.ResultsThe median treatment duration with IGU was 11.3 months. The results demonstrated a significant reduction in the number of attacks over a three-month period (1.3 ± 1.4 vs. 5.8 ± 2.0, P < 0.0001). Furthermore, patients experienced a decrease in attack frequency and an increase in remission duration (78.0(33.8,99.0) days vs. 15.0(13.0,22.0) days, P < 0.0001). The duration of each attack was also shortened (2.1 ± 0.7 days vs. 2.5 ± 0.8 days, P=0.0042). Only one patient discontinued IGU due to gastric upset.ConclusionIguratimod has demonstrated favorable efficacy and safety in the treatment of patients with PR who have not responded adequately to MTX and HCQ, which needs to be further confirmed.